A Randomized Study Comparing Video-Based Mindfulness-Based Cognitive Therapy with Video-Based Traditional Cognitive Behavioral Therapy in a Sample of Women Struggling to Achieve Orgasm. (6th December 2019) - Adam, Françoise; De Sutter, Pascal; Day, James; Grimm, Elise
Abstract: Introduction: This study examines the effectiveness of integrating mindfulness-based techniques within therapy for women suffering to achieve orgasm. Although widely applied in psychotherapy, this approach has only recently been introduced in the treatment of female sexual dysfunction. Aim: To compare the effectiveness of a video-based self-administered treatment, rooted within the cognitive behavioral treatment (CBT) framework, with a video-based self-administered mindfulness treatment applying cognitive behavioral sexual therapy (mindfulness-based cognitive therapy), the latter of which was specifically created to increase women's ability to achieve orgasm. Methods: A convenience sample of 65 women suffering from difficulties to achieve orgasm, aged 18 to 58 years (mean = 32.66, standard deviation = 9.48), were randomly allocated using a randomization procedure to either a mindfulness-based cognitive therapy (N = 35) or CBT (N = 30) group. Each participant completed questionnaires before and after the start of treatment and 2 months after its completion. Main Outcome Measure: We applied repeated-measure general linear models to compare the 2 groups (ie, between participant factor) on each dependent variable across time (ie, the within-participant factor). Compare mean analyses for paired samples were only conducted when the interaction effect between condition and time was significant (ie, P <.05). Results: Statistical analyses show that women in both groups presented increased sexual functioning ( P = .001) and decreased sexual distress ( P < .001), as well as improved desire, arousal, orgasm, and sexual satisfaction ( P < .05) after their respective treatments. Contrary to our hypothesis, significant reductions in sexual pain were only observed in CBT participants. Clinical Implications: To the best of our knowledge, this is the first study to apply a randomized allocation procedure to evaluate the effectiveness of a video-based mindfulness intervention for women struggling to achieve orgasm. These results should guide clinicians' decisions with respect to evaluating the relevance and the real added value of proposing mindfulness exercises to their patients with such difficulties. Conclusion: When women suffering from difficulties to achieve orgasm are randomly assigned to a mindfulness group or an active control, improvements in sexual functioning and reductions in sexual distress can be observed after both treatments.